THE FUTURE OF LAW FROM THE JURISPRUDENCE PERSPECTIVE FOR EXAMPLE :THE INFLUENCE OF SCIENCE & TECHNOLOGY TO LAW, AI LAW - Rehna Gul; Abdallah Mohamed Othman El Nofely (Journal Equity of Law and Governance, 2021)
The field of law is as old as the human civilization. In the ancient Holy Scriptures, the laws of humans, God made Laws, laws of nature, cultural laws, trade laws etc. have been discussed around the world. Even in the stone ages humans were following certain principles and laws which were the basis of law. This article touches the historical perspective, present scenario and future of law. Especially the use of technology in law has brought a revolutionary change in recent decades. The computers, cell phones, social media, internet as a whole, Google play store applications, laptops, i pods and various other devices have made significant changes in old practices and present-day practices in the field of law. Hence, the research aim is a consideration material in making future laws about AI in order to protect Artificial Intelligence users around the world. The research methods and techniques have been made simple. This is a fast world in which we are living. No one has time for anything in this era. With the use of technology many time-consuming activities can be performed in minutes and seconds in this era. We are heading in a direction of more human friendly and time saving environment. Although humans in different parts of the world have different cultures, norms, ethics, eating habits, religions, physical appearances and opinions but there are certain norms and international practices which are widely accepted around the world.